The Ground of Covenant Community and the Righteous Scandal of Christian Love for the World - Samuel Logan, James (Theology today, 2019)
The Ground of Covenant Community lies in the Righteous Scandal of Christian Love for the World. And Jesus is the Most Supreme Scandal to which Christians owe their devotion, that is, their active faith and fidelity in the form of a rugged and sublime love for "the least of these" in temporal life and history.